Economic and environmental evaluation of design for active disassembly. (1st January 2017) - Peeters, Jef R.; Vanegas, Paul; Dewulf, Wim; Duflou, Joost R.
Abstract: Prior research has demonstrated that a disassembly based end-of-life (EoL) treatment for electronic products is characterized by the highest recovery rates for precious metals (PMs) and non-commodity plastics, such as flame retardant plastics. Nonetheless, EoL electronic products are nowadays also commonly recycled without disassembly in different types of size-reduction based treatments or in an integrated PM smelter-refinery. This disparity of recycling processes adopted worldwide resulted in a high uncertainty on the EoL treatment processes that will be adopted for discarded electronic products. As a result, governments, original equipment manufacturers and recycling companies struggle to determine the economic and environmental value of design for disassembly. For this reason, a methodology is presented to calculate the Composite Rate of Return (CRR) on investing in design for disassembly and the resulting environmental impacts. This methodology is applied to evaluate the economic and environmental benefits of implementing three types of active fasteners for eleven electronic products which are available in both a product service system (PSS) and a traditional sales oriented business model. The performed analyses demonstrate that the preferred EoL treatment, as well as the economic and environmental benefits of implementing design for active disassembly, strongly depends on several product properties and boundary conditions. Based on the performed sensitivity analysis, the application of active pressure and temperature sensitive fasteners is expected to be only economically viable for products placed on the market in a PSS context, in which they will be separately collected with a high collection rate. Furthermore, impulse sensitive elastomer based fasteners are characterized with the highest rate of return and considered to be suited for both products sold in a traditional sales oriented business model and for products used in a PSS. Highlights: A methodology is presented to quantify the benefits of design for demanufacturing. This methodology is applied to eleven distinct electronic products. Environmental benefits of design for demanufacturing are product dependent. Pressure and temperature sensitive fasteners are economically viable for product service systems. Impulse sensitive fasteners are characterized with the highest rate of return.